Propagation of mycotoxigenic fungi in maize stores by postharvest insects - Lamboni, Y.; Hell, K. (Springer, 2009)
Maize pests feeding on grains can transmit with their movement fungi harmful to human and animal health. The aim of the present work was to study the immigration and the dynamics of storage pests in traditional African maize granaries and the fungal spectrum associated with these insects. Treatments were (i) maize cobs protected just after pollination with gauze and stored thereafter, and (ii) unprotected maize cobs as controls. Eight different species of insects were identified in stores. No Prostephanus truncatus (Horn) was found in ‘protected’ maize during the 6 months of storage, but their mean number reached 239 individuals per kilogram after just 3 months of storage in the ‘unprotected’ stores. Similarly, significantly more Sitophiluszeamais (Motschulsky) were recovered from the unprotected than the protected maize treatment. Nine fungal species were found to be associated with the storage insects. On ‘non-protected’ cobs the genus Fusarium (36.05%) was the most frequently identified, followed by Penicillium (23.50%), Rhizoctonia (5.65%) and Aspergillus (3.95%). On protected cobs, Rhizoctonia sp. was most frequent (16.76%), followed by Fusarium spp. (16.62%), Penicillium spp. (8.24%) and Aspergillus spp. (2.33%). The toxigenic species encountered were Aspergillus flavus Link, Aspergillus parasiticus Speare and Fusarium verticillioïdes (Sacc.). Cathartus quadricollis (Guérin) appeared to carry more fungi towards the store, mainly Penicillium spp. (51.47%), Aspergillus spp. (46.56%) and Fusarium spp. (32.01%). Storage pests, in particular C. quadricollis and S. zeamais, play an important role in the contamination of maize with fungi, especially those that produce toxins.